USING QUIZLET APPLICATION WITH FLASHCARDS FEATURE TO TEACH EFL VOCABULARY - Pirda Sarantika; Endang Susilawati; Ikhsanudin (LPPM Universitas PGRI Jombang, 2025)
The purpose of this study was to determine the use of the Quizlet application on students' vocabulary mastery. The research design used was Pre-experimental, with a pre-test and post-test design. This research was conducted at SMPN 26 Pontianak City. The population in this study was 123 students divided into 4 classes and the number of samples taken was 1 class. The technique used to determine the research sample was cluster random sampling. Where researchers collected data through measurement tests, namely pre-test and post-test. The results showed an average pre-test score of 60.67 and an average post-test score of 71.83. On the other hand, data analysis using SPSS produced a t-value in the paired t-test of 10.83, higher than the t-table value of 1.699 with 29 degrees of freedom. This analysis concluded that the effect of using the Quizlet application was 1.94, higher than 1.00. It was concluded that the effect size (ES) was greater than 1.00 (1.94 > 1.00). So it was included in the strong influence. This shows that students who were taught with the Quizlet application achieved much higher achievement than before used the application.